Beneficiary Fraud and Demand Guarantees - Kelly Louw, Michelle (Potchefstroom Electronic Law Journal, 2022)
It is settled in South African and English law that for the fraud exception to apply to demand guarantees or letters of credit the fraud must have been committed by the beneficiary (or his agent with the beneficiary’s knowledge) and not by a third party. Even where the fraud relates to a forgery or materially fraudulent document, the fraud must have been committed by the beneficiary for the exception to apply. This is in contrast with American law, where the fraud relating to forgeries and materially fraudulent documents does not necessarily have to be committed by the beneficiary. This contribution considers the law in this regard in these three jurisdictions.